THE EFFECT OF DIGITAL LITERACY AND DIGITAL DIVIDE ON E-GOVERNMENT ADOPTION - Thominathan Santhanamery; Angayarkanni Ramaiah; Dalili Iznie Shafie; Marwan Milhem, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The Malaysian government has launched MyDIGITAL as a national initiative to transform Malaysia into a digitally enabled and technology-driven high-income nation. The digital economy was acknowledged as a key economic growth area. The six strategic thrusts under MyDIGITAL are in line with the national development policies under the 12th Malaysian Plan. The implementation of the Malaysia Digital Economy Blueprint will strengthen the foundation of digital adoption, drive inclusive digital transformation, and finally, make Malaysia a digital content and cyber security leader in the regional market. Thus, this study investigates the newly introduced Digital Road Tax (e-LKM) and Digital Driving License (e-LMM) online renewal through the MyJPJ Digital Platform. The implementation, adoption, and use of e-government have represented a challenge, especially in our country, due to two main challenges i.e. digital literacy, and the digital divide. Digital literacy encompasses the skills and ability to use digital communication tools and networks to access, manage, integrate, evaluate, and create information. Digital Divide on the other hand is defined as the gap between individuals who have access to IT knowledge and resources and those who do not. This research will evaluate the adoption of government facilities from the citizens' perspective using an extended Technology Acceptance Model (TAM), based on the assumptions that citizens with high literacy levels and a low digital divide will have a higher adoption rate of e-government services. Data will be collected through a structured questionnaire from drivers in the northern region of Malaysia namely Penang, Kedah, and Perlis. Data will be tested using SPSS and PLS-SEM. The major findings of this study will be on the effect of digital literacy and the digital divide on the adoption of e-government services and the net benefits of e-government.